Hard to break : why our brains make habits stick - Poldrack, Russell A. (Princeton University Press, 2021)
The neuroscience of why bad habits are so hard to break-and how evidence-based strategies can help us change our behavior more effectivelyWe all have habits we'd like to break, but for many of us it can be nearly impossible to do so. There is a good reason for this: the brain is a habit-building machine. In Hard to Break, leading neuroscientist Russell Poldrack provides an engaging and authoritative account of the science of how habits are built in the brain, why they are so hard to break, and how evidence-based strategies may help us change unwanted behaviors.Hard to Break offers a clear-eyed tour of what neuroscience tells us about habit change and debunks "easy fixes" that aren't backed by science. It explains how dopamine is essential for building habits and how the battle between habits and intentional goal-directed behaviors reflects a competition between different brain systems. Along the way, we learn how cues trigger habits; why we should make rules, not decisions; how the stimuli of the modern world hijack the brain's habit machinery and lead to drug abuse and other addictions; and how neuroscience may one day enable us to hack our habits. Shifting from the individual to society, the book also discusses the massive habit changes that will be needed to address the biggest challenges of our time.Moving beyond the hype to offer a deeper understanding of the biology of habits in the brain, Hard to Break reveals how we might be able to make the changes we desire-and why we should have greater empathy with ourselves and others who struggle to do so.